Selective Isolation of Rare Actinomycetes from Soil - O. N. Sineva; L. P. Terekhova (Антибиотики и Химиотерапия)
Many diverse methods for selective isolation of actinomycetes are used in discovery of organisms producing biologically active substances, as well as in ecological studies. Methods for isolation of rare actinomycetes from soil are reviewed.